2012
DOI: 10.1111/j.1365-2702.2011.04017.x
|View full text |Cite
|
Sign up to set email alerts
|

Creating continuity out of the disruption of a diagnosis of HIV during pregnancy

Abstract: We propose that appropriately educated nursing and midwifery staff could facilitate the 'meaning making' process that is required for newly diagnosed HIV positive persons to find a subjective sense of well-being in their lives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
52
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(57 citation statements)
references
References 22 publications
4
52
1
Order By: Relevance
“…However, the effect sizes observed in the relationships between the maternal-fetal attachment model and these maternal health behaviors ranged, respectively, from medium to medium-large. These findings offer only partial support to the study's hypothesis; however they add emerging credence to similar associations suggested in the qualitative research literature (Ciambrone et al, 2007;D'Auria et al, 2006;Kelly et al, 2012;Njie-Carr et al, 2013). It also suggests potential benefits in attending to the relationship a woman has with her unborn child perhaps as an additional component of her prenatal care to possibly help resolve her struggles with health behaviors.…”
Section: Associations Between Maternal-fetal Attachment and Health Bementioning
confidence: 44%
See 4 more Smart Citations
“…However, the effect sizes observed in the relationships between the maternal-fetal attachment model and these maternal health behaviors ranged, respectively, from medium to medium-large. These findings offer only partial support to the study's hypothesis; however they add emerging credence to similar associations suggested in the qualitative research literature (Ciambrone et al, 2007;D'Auria et al, 2006;Kelly et al, 2012;Njie-Carr et al, 2013). It also suggests potential benefits in attending to the relationship a woman has with her unborn child perhaps as an additional component of her prenatal care to possibly help resolve her struggles with health behaviors.…”
Section: Associations Between Maternal-fetal Attachment and Health Bementioning
confidence: 44%
“…Nonetheless, they reported that the health of the fetus, the desire to protect the fetus from their own infection, and the motivation to prevent mother-to-child transmission were the primary reasons women offered to account for their better adherence during pregnancy, compared to the period after childbirth (Ekama et al, 2012;Mellins et al, 2008;Michel et al, 2012;Nachega et al). Similar themes, such as getting tested and adhering to ART medication early in pregnancy to protect the health of the fetus and/or proactively guard the women's own health, clearly emerge among the findings of two, one national another international, qualitative studies (Kelly et al, 2012;Njie-Carr et al, 2012). The explanations and themes expressed by HIV-infected pregnant women participating in these studies closely allude to their experience of maternal-fetal attachment.…”
Section: Maternal Health Behaviors Among Pregnant Women With Hiv/aidsmentioning
confidence: 79%
See 3 more Smart Citations